GeS2–Ga2S3–LiCl Glass System: Electrical Conductivity and Structural Considerations. (21st March 2016) - Cozic, Solenn; Bréhault, Antoine; Le Coq, David; Usuki, Takeshi
Abstract : Chalcogenide samples were synthesized by melting‐quenching method in the GeS2 –Ga2 S3 –LiCl system to determine its vitreous domain. Different series were investigated by varying either the GeS2 /Ga2 S3 ratio or the molar content of LiCl. The study allows to establish that a maximum of 20 mol% of LiCl can be added in the glass composition. The glass transition and onset crystallization temperatures ( T g and T x ) and density have been determined and the thermal stability is discussed following the ΔT ( T x – T g ) parameter. The electrical conductivity of glasses increases with the LiCl content and reaches a maximum of 1.2 μS/cm at room temperature. Finally, correlations between the conductivity and the structure analyzed by Raman spectroscopy were highlighted.